Pemenuhan Hak Anak Terhadap Perlindungan Hukum Terkait Dengan Undang-Undang Nomor 23 Tahun 2002 Di Balai Rehabilitasi Sosial Anak Memerlukan Perlindungan Khusus (BRSAMPK) Handayani Jakarta - Intan Pertiwi; Idzan Fautanu; Marni Emmy Mustofa (JOURNAL of LEGAL RESEARCH, 2021)
Deviations from norms that commonly occur in social life are deviations from legal norms which are called crimes. Crime as a social phenomenon takes various forms. Starting from the theft of sandals, theft of valuables, robbery, murder, acts of social violence in the family sphere, to violence that occurs among students. Fulfillment of the rights of correctional students as inmates is very important, especially when there is LPKA as an institution or place for children to serve their criminal period. Children who are in conflict with the law are the nation's next generation whose rights must still be fulfilled while they are in this Child Special Guidance Institute. This is because correctional students are also classified as legal subjects. The legal provisions discussed in this paper are only the fulfillment of children's rights at the Center for Social Rehabilitation of Children Require Special Protection Handayani Jakarta. Basically the fulfillment of the rights given has been regulated in Law Number 23 of 2002 concerning Child Protection, but in reality the fulfillment of children's rights at the Child Social Rehabilitation Center Requires Special Protection Handayani Jakarta has not been fully fulfilled.Keywords: Fulfillment of Children's Rights; Coaching and Services; Legal protection